Tomasz Jeż, Danielis Sartorii Musicalia Wratislaviensia, Warszawa 2017 (= Fontes Musicae in Polonia A/I) - Scott, Allen (Muzyka, 2018)
Recenzja książki: Tomasz Jeż, "Danielis Sartorii Musicalia Wratislaviensia", Warszawa 2017 (= Fontes Musicae in Polonia A/I)